Immunogenicity of anti-TNF-α biotherapies. I. Individualized medicine based on immunopharmacological evidence - Bendtzen, Klaus (Frontiers in Immunology, 2015)
Specific inhibition of the cytokine, tumor necrosis factor-α (TNF), has revolutionized the treatment of patients with several autoimmune diseases, and genetically engineered anti-TNF antibody constructs now constitute a heavy medicinal expenditure in many countries. Unfortunately, up to 30% of patients do not respond and about 50% of those who do loose response with time. Furthermore, safety may be compromised by immunogenicity with the induction of anti-drug-antibodies (ADA). Assessment of drug pharmacokinetics and ADA is increasingly recognized as a requirement for safe and rational use of protein drugs. The use of therapeutic strategies based on anti-TNF drug levels and ADA rather than dose-escalation has also proven to be cost-effective, as this allows individualized patient-tailored strategies rather than the current universal approach to loss of response. The objective of the present article – and the accompanying article – is to discuss the reasons for recommending assessments of circulating drug and ADA levels in patients treated with anti-TNF biopharmaceuticals and to detail some of the methodological issues that obscure cost-effective and safer therapies.